Forefront of Na+/Ca2+ Exchanger Studies: Physiology and Molecular Biology of Monovalent Cation Sensitivities in Na+/Ca2+ Exchangers - Akira Uehara; Takahiro Iwamoto; Yuki Nakamura; Issei Imanaga (Journal of Pharmacological Sciences, 2004)
Sensitivities of the reverse-mode Na+/Ca2+ exchange activity measured as the Na+i-dependent Ca2+ uptake to extracellular monovalent cations K+, Li+, and Na+ were compared between the K+-dependent (NCKX2) and the K+-independent Na+/Ca2+ exchanger (NCX1) overexpressed in a fibroblast cell. Interestingly, the exchange activity of NCKX2 was not influenced by Li+ while it was increased by K+. On the contrary, the activity of NCX1 was increased by Li+. Thus, the cation sensitivities to K+ and Li+ markedly differed between NCKX2 and NCX1. In addition, Na+ exerted a significantly smaller inhibitory effect on the activity in NCKX2 than in NCX1. The Na+/Ca2+ exchange activities of NCKX2 and NCX1 are considered to be regulated differentially via the respective binding site domains that have distinct sensitivities to the external monovalent cations. Keywords:: Na+/Ca2+ exchanger (NCX), K+-dependent NCX (NCKX)2, NCX1